Legal Certainty for Halal Tourism in the Implementation of Islamic Sharia in Aceh Province - Zulfiyanda, Zulfiyanda; Ramlan, Ramlan; Wajdi, Farid (JURNAL AKTA, 2025)
Halal tourism in Aceh holds great potential in supporting economic growth, enhancing community welfare, and preserving Sharia values within the tourism industry. Through the implementation of Aceh Qanun No. 8 of 2013 on Tourism, the government has made efforts to develop infrastructure, services, and policies that support halal tourism. This study analyzes the implementation of halal tourism in Aceh, the challenges faced, and optimization strategies that can be applied to strengthen the competitiveness of this tourism destination. The findings indicate that although Aceh has various advantages such as supporting infrastructure, a strong Islamic cultural identity, and proactive government policies, challenges still exist in global promotion, the availability of internationally standardized halal tourism facilities, and perceptions of non-Muslim tourists. Therefore, a strategic approach is required, including improving infrastructure quality, digital-based tourism promotion, collaboration with the global tourism industry, and strengthening human resource capacity in this sector. With these strategic measures, Aceh can further solidify its position as a leading halal tourism destination that is not only economically beneficial but also contributes to the broader welfare of society.